Differences in The Effectiveness of Lemon Juice (Citrus limon) and Apple Cider Vinegar (Malus pumila Mill) in Whitening Tooth Enamel - Rina Permatasari; Carenina Claudia (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2025)
Background: The stability of tooth enamel colour can be affected by foods and beverages due to its fluid absorption properties. Dental bleaching could fix it, but chemical teeth whitening agents have irritating and sensitive effects, therefore, it’s needed to find alternatives for natural teeth whitening ingredients that are safer and affordable. Lemon juice (Citrus limon) and apple cider vinegar (Malus pumila Mill) contain malic acid, which are natural teeth whitening agents. To prove the effect of lemon juice and apple cider vinegar in changing the colour of tooth enamel. Methods: Thirty samples of permanent canine teeth, randomly divided into 3 groups, soaked for 5 days in lemon juice (n=10), apple cider vinegar (n=10), and distilled water (n=10). Measurements were taken using VITA Easyshade V to see the lightness value. Results:The lightness value of lemon juice has the highest significance (p=0,003) among all treatment groups. Conclusion: Lemon juice showed a better number of lightness which means it has better efficiency on teeth whitening rather than apple cider vinegar.